BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK IMUNISASI PENTAVALEN BOOSTER DI WILAYAH KERJA PUSKESMAS MANGUNSARI SALATIGA - Anisah Munawaroh; Syamsulhuda BM Syamsulhuda BM; Bagoes Widjanarko (Jurnal Kesehatan Masyarakat (Undip), 2016)
Pentavalent immunization is the immunization to prevent Diptheria, Pertisis, Tetanus, Hepatitis B and pneumonia. In Indonesia 32.1% were immunized but not completely. 8.7% were never immunized. The research purpose was to analyze some factors that were related to the booster pentavalent immunization practices in the Mangunsari Puskesmas Salatiga City. The method that was used was quantitative with a cross sectional research design. The population in this study were all mothers who had babies aged 18 – 36 months by of March 2016. Probality sampling, also known as proportional random sampling was use on 59 people. Data is analyzed using univariat and bivariate with Chi Square test with a significance level of 0.05. The results showed that women implementing who the booster pentavalent immunization practices is 73%. The univariate analyzis showed that age responden ≤ 35 years old (74,6%), basic education (51%), do not working (59%), well knowledge (61%), being supportive to the booster pentavalent immunization practices (81%), care facilities affordability (88%), do not get family support (59,3%), get health workers support(72,9%), get care facilities affordability (86,4%).The Chi square test result showed that the factors ssociated with the practice of booster pentavalent immunization are knowledge (p-value = 0.039), attitude (p-value = 0.006), family support (p-value = 0.0001), health professionals support (p-value = 0.023). The variables that are not related to the booster pentavalent immunization practices are age (p-value = 1.000),  job (p-value = 0.996), education level (p-value = 0.424), care facilities affordability (p-value = 0.375) and health workers / public figures support (p-value = 0.104).